Unusual unilateral presentation of pachydermodactyly: a case report - Ulusoy, Hasan; Tas, Nevsun Pihtili; Akgol, Gurkan; Gulkesen, Arif; Kamanli, Ayhan (Springer Heidelberg, 2012)
Pachydermodactyly is a rare digital fibromatosis characterized by asymptomatic fusiform soft-tissue swellings of the proximal interphalangeal joints of the hands. It usually affects healthy adolescent males with a negative family history. As a rule, clinical presentation of the disease is bilateral and symmetrical enlargement of the joints. So it can be misdiagnosed with inflammatory rheumatic diseases, especially with juvenile chronic arthritis. A prompt clinical diagnosis of the disease would prevent inappropriate treatment with immunosuppressive agents or steroids and unnecessary expensive diagnostic procedures such as biopsy or magnetic resonance imaging. Once diagnosed, patients should be advised in order to avoid repetitive traumas of the hands, rubbing and cracking of the fingers, obsessive-compulsive use of computer and video games. The joint outcome is always benign. Here, we report a case of pachydermodactyly differs from the typical clinical picture of pachydermodactyly in the unilateral distribution of the lesions.
Keywords: Pachydermodactyly; Digital fibromatosis; Painless joint swelling; Obsessive compulsive disorder